Genetic Variants of Glycogen Metabolism Genes Were Associated With Liver PDFF Without Increasing NAFLD Risk - Yang, Liu; Sun, Zewen; Li, Jiuling; Pan, Xingchen; Wen, Jianping; Yang, Jianli; Wang, Qing; Chen, Peng (Frontiers in Genetics, 2022)
Abstract Background/aims: The storage amount of liver glycogen could affect the liver fibrosis assessment made by MRI based methods. However, it remained unclear whether glycogen amount could bias the estimation of liver fat content by PDFF. In this study, we aimed to investigate whether glycogen metabolism gene variants could contribute to the bias of PDFF by genetic association. Methods: We conducted an association study of the glycogen metabolism genes based on the PDFF data of 11,129 participants in the UK Biobank. The effect of the SNPs in these genes on NAFLD was estimated by a meta-analysis of the available NAFLD case-control studies. Results: We identified significant associations of the SNPs near genes encoding glycogen phosphorylase (PYGM and PYGL) and synthase (GYS2) with PDFF (FDR corrected p value <0.05). The genes encoding the regulatory proteins of glycogenolysis (PHKB, CALM2/3), glucose transporter (SLC2A1) and glucose kinase (GCK) were also associated with PDFF. The SNP rs5402 of SLC2A2 and rs547066 of PYGM were associated with NAFLD (p <0.05) with others being insignificant. Except for PYGM gene, the PDFF associated SNPs showed no associations with NAFLD. In addition, the burden tests of rare variants in these genes were not significant after FDR correction. Conclusions: Liver glycogen metabolism genes associated with PDFF were not associated with NAFLD, which implicated a potential bias effect of glycogen storage on the quantification of liver fat content by PDFF.